Optimum irrigation water allocation and crop distribution using combined Pareto multi-objective differential evolution. Issue 1 (1st January 2018) - Ikudayisi, Akinola; Adeyemo, Josiah; Odiyo, John; Enitan, Abimbola
Abstract: This paper presents the application of a new evolutionary algorithm technique called combined Pareto multi-objective differential evolution (CPMDE) to optimize irrigation water allocation and crop distribution under limited water availability with three different crops (maize, potatoes and groundnut) planted on a 100 ha farmland at Vaalharts irrigation scheme, South Africa. The algorithm combines methods of Pareto ranking and Pareto dominance selections to implement a novel selection scheme at each generation. The ability of CPMDE in solving unconstrained, constrained and real-world optimization problems was demonstrated. The two objectives of the model are to maximize total crop net benefit (NB) over a planting season while minimizing total irrigation water allocation. A set of non-dominated solutions with the high NBs at lower irrigation water allocation for three crop types was obtained, and compromise programming approach was used in evaluating the most favourable solution. The best solution shows that maize produced the highest crop yield under limited water allocation in the study area. Comparing this result with that of a previous study which adopted a multi-objective optimization algorithm called multi-objective differential evolution algorithm, CPMDE is a good and robust alternative algorithm suitable for resolving crop distribution under limited water availability.